Accounting, taxation and control of the activities of economic entities in the conditions of crisis phenomena - Derii, Vasyl; Muravskyi, Volodymyr; Pochynok, Nataliia; Sysiuk, Svitlana; Zarudna, Nataliia (Herald of Economics, 2022)
Analytical note based on the results of a scientific and practical round table with international participation (Ternopil, ZahidnoukrainskyNational University, June 15, 2022) on June 15, 2022, a scientific and practical round table was held with international participation on the topic